PENGARUH GAYA KEPEMIMPINAN DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT XPEL INDONESIA JAKARTA BARAT - Mustakim; Kamsidik (Jurnal Menara, 2026)
This study aims to determine the effect of Leadership Style and Work Facilities on Employee Performance at PT. XPEL Indonesia, West Jakarta, both partially and simultaneously. This study used a quantitative approach with a saturated sampling method. Therefore, the entire population of 32 employees served as the sample. The research data were analyzed using simple and multiple linear regression, t-tests, F-tests, correlation coefficients, and coefficients of determination. Research Results The data analysis method used is multiple linear regression using the SPSS version 25 application. The regression equation Y = 12.010 + 0.235 X1 + 0.599 X2, (F Test) on the Leadership Style variable (X1) and the Work Facilities Variable (X2) shows a calculated f value > f table, namely 12.247 > 3.330 and has a sig value of 0.000 < 0.05, So it can be concluded that the Leadership Style variable (X1) and the Work Facilities variable (X2) together (Simultaneously) have a significant effect on the Employee Performance variable (Y) at PT XPEL Indonesia West Jakarta.